The Effect of Profitability, Liquidity, and Leverage on Stock Prices of Banking Sector Companies Listed on the Indonesia Stock Exchange 2019–2023 - Abdul Azis; Nasya Putri Rahayu (SEAN Institute, 2026)
The purpose of this study is to analyze the effect of profitability, liquidity, and leverage on stock prices of banking companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The independent variables in this study are Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Debt to Equity Ratio (DER), while the dependent variable is stock price. This study uses a quantitative method with secondary data obtained from company financial statements and stock prices. The sampling technique used was purposive sampling, resulting in 23 companies that met the research criteria. After the process of identifying and eliminating outliers, the final sample consisted of 13 banking companies with a total of 65 observations. Data analysis was conducted using panel data regression with the assistance of EViews 14 software. Based on the Chow test and Hausman test results, the best model used was the Fixed Effect Model (FEM). The results showed that partially, Return on Assets (ROA) and Debt to Equity Ratio (DER) had no significant effect on stock prices, while Loan to Deposit Ratio (LDR) had a positive and significant effect on stock prices. However, simultaneously, ROA, LDR, and DER significantly affected the stock prices of banking companies